Pressure‐Tailored Self‐Driven and Broadband Photoresponse in PbI2. Issue 12 (9th November 2022) - Li, Zonglun; Li, Quanjun; Li, Haiyan; Tian, Fuyu; Du, Mingyang; Fang, Sixue; Liu, Ran; Zhang, Lijun; Liu, Bingbing
Abstract: Photoelectric devices based on the photothermoelectric (PTE) effect show promising prospects for broadband detection without an external power supply. However, effective strategies are still required to regulate the conversion efficiency of light to heat and electricity. Herein, significantly enhanced photoresponse properties of PbI2 generated from a PTE mechanism via a high‐pressure strategy are reported. PbI2 exhibits a stable, fast, self‐driven, and broadband photoresponse at ≈980 nm. Intriguingly, the synergy of the photoconductivity and PTE mechanism is conducive to enhancing the photoelectric properties, and extending the detection bandwidth to the optical communication waveband (1650 nm) with an external bias. The dramatically enhanced photoresponse characteristics are attributed to narrowing of the band gap and a significantly decreased resistance, which originate from the enhancement of atomic orbital overlap owing to pressure‐induced Pb‐I bond contraction. These findings open up a new avenue toward designing self‐driven and broadband photoelectric devices. Abstract : A pressure‐tailored broadband photoresponse with a self‐driven operation capacity dominated by the photothermoelectric (PTE) mechanism is achieved under 520 to 980 nm local laser illumination in PbI2 . The synergy of the photoconductivity and PTE mechanism is conducive to extend the detection bandwidth to the optical communication waveband. These findings provide some new insights into designing self‐driven and broadband photoelectric devices.